2014
DOI: 10.1186/1471-2296-15-141
|View full text |Cite
|
Sign up to set email alerts
|

Practice guidelines in the context of primary care, learning and usability in the physicians’ decision-making process – a qualitative study

Abstract: BackgroundDecision-making is central for general practitioners (GP). Practice guidelines are important tools in this process but implementation of them in the complex context of primary care is a challenge. The purpose of this study was to explore how GPs approach, learn from and use practice guidelines in their day-to-day decision-making process in primary care.MethodA qualitative approach using focus-group interviews was chosen in order to provide in-depth information. The participants were 22 GPs with a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
2
13
0
1
Order By: Relevance
“…A shift in the focus from sociocognitive behavioural theories to factors which impact clinical reasoning [53], specifically regarding decision-making theory, may be required. One such theory is the dual process theory (DPT), which describes two types of decision-making: system 1, a fast, intuitive, automatic approach which is not cognitively demanding but can be inaccurate, and system 2, a slow, conscious, analytical approach [53–55]. When faced with time pressures, lack of confidence or problems that are perceived to be routine or certain, clinicians may favour system 1 decision-making [53].…”
Section: Discussionmentioning
confidence: 99%
“…A shift in the focus from sociocognitive behavioural theories to factors which impact clinical reasoning [53], specifically regarding decision-making theory, may be required. One such theory is the dual process theory (DPT), which describes two types of decision-making: system 1, a fast, intuitive, automatic approach which is not cognitively demanding but can be inaccurate, and system 2, a slow, conscious, analytical approach [53–55]. When faced with time pressures, lack of confidence or problems that are perceived to be routine or certain, clinicians may favour system 1 decision-making [53].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, deliberative learning, such as follow-up discussions after observations, are needed even more to benefit from observing. Another advantage of deliberative dialogue is that it not only leads to a learning effect for the observer, who asks why the acting clinician showed certain EBM behaviour, but it can also foster the actor's reflection on and explication of their own tacit knowledge and thus enhance evidence-based decision-making in both parties [37]. More research needs to be done on the best ways to train and educate both supervisor and trainee to be engaged in such dialogues in an optimal manner.…”
Section: Actor-related Aspects: Mindlines Hamper Correct Observationmentioning
confidence: 99%
“…Other studies have found that many school-aged children with doctor-diagnosed asthma and atopic diseases are both under-diagnosed and under-treated (21,(23)(24)(25)(26). Early diagnosis and better control are recommended from the European partnership of airways to prevent the consequences of allergies and asthma as chronic diseases (27).…”
Section: Self-reported Current Asthmamentioning
confidence: 99%